Expulsion mechanism of the substrate-translocating subunit in ECF transporters - Thangaratnarajah, Chancievan; Nijland, Mark; Borges-Araújo, Luís; Jeucken, Aike; Rheinberger, Jan; Marrink, Siewert J.; Souza, Paulo C. T.; Batista Paulino, Cristina; Slotboom, Dirk J. (Nature Communications, 2023)
Energy-coupling factor (ECF)-type transporters mediate the uptake of micronutrients in many bacteria. They consist of a substrate-translocating subunit (S-component) and an ATP-hydrolysing motor (ECF module) Previous data indicate that the S-component topples within the membrane to alternately expose the binding site to either side of the membrane. In many ECF transporters, the substrate-free S-component can be expelled from the ECF module. Here we study this enigmatic expulsion step by cryogenic electron microscopy and reveal that ATP induces a concave-to-convex shape change of two long helices in the motor, thereby destroying the S-component’s docking site and allowing for its dissociation. We show that adaptation of the membrane morphology to the conformational state of the motor may favour expulsion of the substrate-free S-component when ATP is bound and docking of the substrate-loaded S-component after hydrolysis. Our work provides a picture of bilayer-assisted chemo-mechanical coupling in the transport cycle of ECF transporters.